Assessment of factors influencing the adoption of public private partnerships in water infrastructure projects in selected municipalities - Fourie, D.J. (David Johannes) (University of Pretoria, 2022)
Thesis (PhD (Public Management and Administration))--University of Pretoria, 2022.